Elucidation of the Nucleophilic Potential of Diazocyclopentadiene - Hartnagel, Manfred; Ofial, Armin R.; Mayr, Herbert (Synthesis, 2022)
Diazocyclopentadiene reacts with benzhydrylium ions (Ar2CH+) to give 2,5-dibenzhydryl-substituted diazocyclopentadienes. The kinetics have been determined photometrically in dichloromethane under pseudo-first-order conditions using diazocyclopentadiene in excess. Plots of the second-order rate constants (log k2) versus the electrophilicity parameters E of the benzhydrylium ions gave the nucleophilicity parameter N = 4.84 and susceptibility sN = 1.06 for diazocyclopentadiene according to the correlation log k(20 °C) = sN(E + N). Diazocyclopentadiene thus has a similar nucleophilic reactivity as pyrrole. Previously reported electrophilic substitutions of diazocyclopentadiene are rationalized by these parameters and new reaction possibilities are predicted.
Keywords: diazo compounds; kinetics; linear free energy relationships; nucleophilicity; reactivity scales